Mengakses Akun Instagram @Nunuzoo dan Pengaruhnya Terhadap Sikap Keagamaan Follower - Muhlisoh; Ade Fadli Fachrul (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
The study entitled the influence of the intensity of accessing the @nunuzoo dakwah instagram account on religious attitudes aims to determine how much influence the use of Instagram social media has on the religious attitudes of its followers. The research conducted is a quantitative research type. The population of the study was the followers of the @nunuzoo instagram account. The research conducted is a quantitative research type. The population of the study was the followers of the @nunuzoo instagram account as many as 431,000 followers with a sampling technique using simple random sampling with the slovin formula, there were 80 respondents. While for primary data using a questionnaire, data processing used by utilizing Microsoft Excel Software. Data analysis in this study used a normality test, a simple linear test, a correlation coefficient test and a determination coefficient test. Based on the results of the study, it shows that there is an influence of the intensity of accessing Instagram on the religious attitudes of followers. With a significant value of 76.6% while the remaining 23.4% is the contribution of other variables not studied by the researcher.